Mangrove diversity and community structure of Mimika District, Papua, Indonesia - Gesang Setyadi; RUDHI PRIBADI; DIAH PERMATA WIJAYANTI; DENNY NUGROHO SUGIANTO (Society for Indonesian Biodiversity, 2021)
Abstract. Setyadi G, Pribadi R, Wijayanti DP, Sugianto DN. 2021. Mangrove diversity and community structure of Mimika District, Papua, Indonesia. Biodiversitas 22: 3562-3571. Despite being one the largest mangrove forest in the world, there are few studies on mangrove diversity and community structure in Mimika, Papua Province. The study collected data from 4 estuaries of Mimika Region, i.e. Kamora, Tipuka, Ajkwa and Minajerwi. Mangrove species, tree diameter at breast height and canopy height data were collected in 10 m x 10 m plot with three replicates for distance, specifically 0, 250, and 500m perpendicular to the riverbank. This study found 66 mangroves species consisting of 20 major, 10 minor, and 36 associate mangrove species. Their density ranged from 577-1,345 trees ha-1 with diversity Shannon-Weiner diversity indices (H’) ranging from 0.62-1.19 and Evenness Index (J’) ranging from 0.09-0.18. The canopy height of the mangrove trees was ranged from 9-42.5 m. The highest density species was Rhizophora apiculata (333 ha-1) followed by Avicennia marina, Bruguiera gymnorrhiza, and Camptostemon schultzii, while B. parviflora, S. alba, and X. granatum were the least dominant. Regarding basal area, R. apiculata and B. gymnorrhiza were the highest with medians of 7,853 cm2 ha-1 and 5,201 cm2 ha-1 respectively. In the low tidal zone area, mangrove was dominated by A. marina, Sonneratia alba and R. mucronata. Medium low to medium high tidal zones were dominated by B. gymnorrhiza, R. apiculata, and B. parviflora. The high tidal zone was more dominated by Nypa fruticans.